2021
DOI: 10.1007/s10461-021-03320-x
|View full text |Cite
|
Sign up to set email alerts
|

“I had Made the Decision, and No One was Going to Stop Me” —Facilitators of PrEP Adherence During Pregnancy and Postpartum in Cape Town, South Africa

Abstract: PrEP is safe and effective but requires adherence during potential HIV exposure, yet the facilitators of long-term maternal adherence are not well understood. We conducted semi-structured interviews with 25 postpartum women who reported high adherence (PrEP use ≥ 25 days in last 30-days and never missed a PrEP prescription in pregnancy/postpartum period) within a PrEP service for pregnant and postpartum women. A thematic approach guided an iterative process of coding and analysis. Themes identified as drivers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For example, having a partner who had not been tested for HIV or whose HIV status was unknown was associated with lower odds of retention. Previous studies have identified that home-based HIV testing is a cost-effective intervention associated with higher uptake of couples testing, higher uptake of male partner testing and improved HIV status disclosure [49][50][51]. As high anticipated stigma is associated with lower PrEP initiation and retention, interventions which aim to engage male partners in HIV prevention through partner testing and counseling, awareness building and adherence support could reduce the consistent barrier faced by pregnant and postpartum women who anticipate stigma or limited support from partners and significant others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, having a partner who had not been tested for HIV or whose HIV status was unknown was associated with lower odds of retention. Previous studies have identified that home-based HIV testing is a cost-effective intervention associated with higher uptake of couples testing, higher uptake of male partner testing and improved HIV status disclosure [49][50][51]. As high anticipated stigma is associated with lower PrEP initiation and retention, interventions which aim to engage male partners in HIV prevention through partner testing and counseling, awareness building and adherence support could reduce the consistent barrier faced by pregnant and postpartum women who anticipate stigma or limited support from partners and significant others.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend including enhanced counselling around PrEP use disclosure among family and partners and adherence clubs or PrEP ambassadors in antenatal and postnatal services to address anticipated and realized stigma. Disclosure of PrEP use to partners and family members may also help to reduce levels of internalized and anticipated stigma [ 51 ]. For example, having a partner who had not been tested for HIV or whose HIV status was unknown was associated with lower odds of retention.…”
Section: Discussionmentioning
confidence: 99%
“…While safety data are reassuring, more data on how best to provide and optimize PrEP use in pregnancy and the postpartum period are needed. There are multiple large‐scale PrEP in pregnancy programs ongoing in South Africa and Kenya [8,14,15]. Effective PrEP protection requires daily PrEP adherence, but little is known about how minor symptoms, which may occur more commonly during pregnancy, overlap with PrEP side effects and could impact PrEP persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Some women were also concerned about partner reactions to their PrEP use. Direct partner education may help address these concerns [ 47 ], and relieve women of the burden of sharing information second‐hand. Though most women had independently decided to use PrEP, there was diversity in partner involvement both before and after the initial decision.…”
Section: Discussionmentioning
confidence: 99%